Bank Concentration and Retail Interest Rates - Sandrine Corvoisier; Reint E. Gropp (European Central Bank (ECB), 2001)
The recent wave of mergers in the euro area raises the question, whether the increase in concentration has at least in part offset the increase in competition in European banking through deregulation. We test this question by estimating a simple Cournot model of bank pricing. We construct country and product specific measures of bank concentration and find that for loans and demand deposits, increasing concentration may have resulted in less competitive pricing by banks, whereas for savings and time deposits, the model is rejected, suggesting increases in contestability and/ or efficiency in these markets. These findings are robust across a wide variety of econometric specifications. Finally, the paper discusses some implications for tests of the effect of concentration on monetary policy transmission
Keywords: L13; G21; B43; 330